Applicability and Variability of Chemical Weathering Indicators and Their Monsoon-Controlled Mechanisms in the Bay of Bengal - Li, Jingrui; Liu, Shengfa; Shi, Xuefa; Zhang, Hui; Cao, Peng; Li, Xiaoyan; Pan, Hui-Juan; Khokiattiwong, Somkiat; Kornkanitnan, Narumol (Frontiers in Earth Science, 2021)
To help understanding the potential relationship between chemical weathering and Indian summer monsoon (ISM) since the last glacial period a gravity core (BoB-56) was retrieved from the central Bay of Bengal (BoB). The data of chemical weathering indexes (CIA, WIP, and αAlNa) used in this study showed general synchronicity with the regional monsoon precipitation and temperature record on precessional scale, indicating existence of control from the ISM on weathering. Corresponding to alteration of warm/cold period during the last deglaciation, obvious simultaneously alteration of higher/lower values of the chemical weathering and terrestrial input proxies’ record support our hypothesis that the ISM driving chemical weathering on the millennial scale. However, a contradiction occurred during the Holocene period, when the ISM precipitation and temperature rose to a higher level, while the alternative indexes unanimously reflected a weaker chemical weathering conditions. In this study, we discussed the applicability of chemical weathering indexes in the BoB during the Holocene period. Besides the possible weakened monsoon during 6–3 ka, recorded by the stalagmite δ18O and Sea Surface Temperature (SST) reconstruction results in the northeastern Indian Ocean, other factors were responsible for this phenomenon, including the grain size effect and distinction between the mountain high land and floodplain low land. The chemical weathering records, during the last glaciation, indicated the presence of control from the ISM on weathering at precessional and millennial scales. While, during the Holocene, they failed to reflect the actual chemical weathering dynamics of the source area. Indeed, a mixture of physical erosion and chemical weathering seems to be representative of the chemical weathering dynamics in the area. Our findings emphasized on the tight connections between the chemical weathering evolution and global-regional climate conditions around the BoB, implying possible ISM-controlled mechanisms during different time scales.